1993
DOI: 10.3349/ymj.1993.34.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wheelchair ergometer training on spinal cord-injured paraplegics

Abstract: The purpose of this study was to investigate the effect of wheelchair ergometer training on spinal cord-injured paraplegics. Eleven male paraplegics with a mean age of 30.9 years (range, 20 to 49 years) participated in the wheelchair ergometer training for the period of 5 weeks. The mean peak heart rate, the mean peak systolic blood pressure and the mean time required for 100m wheelchair propelling at resistance level 1 were significantly decreased at the end of 5 weeks of training as compared with those at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…After reading the 40 papers (LV: PhD student and ET: MSc in Human Movement Science; both experienced in physical therapy research methods), 15 training studies were excluded for the following reasons: other outcome measures, [15][16][17][18][19][20][21][22][23] mixed population, 24,25 the population was not described properly, 26 training of both arms and legs 27 or -as was the case in two papers -the results were already published in other included papers. 28,29 The 25 included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the 40 papers (LV: PhD student and ET: MSc in Human Movement Science; both experienced in physical therapy research methods), 15 training studies were excluded for the following reasons: other outcome measures, [15][16][17][18][19][20][21][22][23] mixed population, 24,25 the population was not described properly, 26 training of both arms and legs 27 or -as was the case in two papers -the results were already published in other included papers. 28,29 The 25 included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…All studies claim significant improvements in muscle strength, but again, no control groups were present in any of the studies involved. Other upper body training studies in spinal cord injury, 16,18,19 all excluded from this review because they lacked data on VO 2peak and PO peak , also reported improvement in muscle strength.…”
Section: Other Outcome Measuresmentioning
confidence: 99%
“…It may be expected that the groups have dierent responses to the training, but these results may be possible because the paraplegic patients in this study were heterogeneous and the standard deviation of HR was greater, involving no signi®cant dierence. 4 However, previous studies have reported in healthy subjects that perceived exertion can be used to control exercise intensity during continuous 9,11,13 or intermittent training.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have found similar ®ndings. 4,7 A dierence in the perception of pain was observed between GXT 1 and GXT 2 between the two groups. The paraplegics seem to feel less pain compared to healthy subjects during exercise.…”
mentioning
confidence: 99%
See 1 more Smart Citation